NAVIGATING ECONOMIC HORIZONS: UNRAVELING THE FINANCIAL LITERACY TAPESTRY AND INVESTMENT TRENDS AMONG ACADEMIC PROFESSIONALS IN VARANASI (International Journal of Food and Nutritional Sciences, 2022)
This study endeavours to cope with a terrific void in the literature by undertaking complete research into the economic literacy and funding behaviour of instructional experts in Varanasi district. Despite their pivotal position in shaping the highbrow and academic panorama, there is a dearth of studies on the monetary dynamics of this specific demographic. They have a look at employing a quantitative study design with a sample length of 182, scrutinizing diverse economic attitudes and behaviours among academic experts. The research technique employs a quantitative method, utilizing a dependent questionnaire to gather facts. Stratified random sampling ensures representation from various strata inside the instructional professional population, enhancing the generalizability of findings. This multifaceted approach presents complete know-how of monetary dynamics in a unique nearby context, contributing treasured insights to both academia and policymaking. The findings screen distinctive factors consisting of gift-centric economic attitudes and the coexistence of diverse monetary behaviours, imparting nuanced insights into the choice-making methods of educational specialists. These insights spotlight the want for targeted monetary training projects tailored to the unique wishes of this demographic. Additionally, they have a look to underscore the importance of knowledgeable policymaking to decorate the monetary well-being of academic experts in Varanasi district.